A proposed assessment tool for measuring the spatial accessibility of libraries in the Philippines using enhanced 2-step floating catchment area (a GIS-based method) - Hernandez, Luke Martin; Dorado, Dan Anthony D. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2024)
This study introduces a proposed GIS-based assessment tool designed to measure the spatial accessibility of libraries in the Philippines, leveraging the Enhanced Two-Step Floating Catchment Area (E2SFCA) method. Originally developed for healthcare accessibility, the E2SFCA method is adapted in the study to evaluate library services, recognizing libraries as vital community hubs. The E2SFCA method assesses whether library services are sufficient for the population served by the libraries while giving weight to nearer populations over farther ones.

Findings from the Quezon City Public Library (QCPL) System highlight significant disparities in library accessibility. This research underscores the importance of data-driven decision-making in addressing accessibility gaps and improving library services. This tool provides a comprehensive framework that policymakers and stakeholders can use to ensure fair and equal access to library resources across the Philippines.
Thesis
Keywords: Geographic information systems